IMPLEMENTASI PRINSIP – PRINSIP KEBIJAKAN PENDIDIKAN ANAK USIA DINI - Savira; Afiyah Firiyani; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the principles of early childhood education and early childhood education. The principles of PAUD (Early Childhood Education) policy and early childhood education policy are an important background in many studies that focus on early childhood education. Implementing these principles generally covers various aspects, including accessibility, quality of education, curriculum that is appropriate to child development, support for children with special needs, training for educators, and involvement of parents and communities in the learning process. ECCE policies are often designed to ensure that children have equal access to quality education from an early age. It also aims to prepare children to enter formal education with a strong foundation in their physical, cognitive, emotional, and social development.